Analysis of School Financial Management in the Context of Tax Accounting: A Case Study at SMP Negeri 3 Hilisalawa'ahe - Laia, Tutihandayani; Nasution, Minasari (Jurnal Akuntansi Hukum dan Edukasi, 2024)
Schools as educational units manage their finances independently and are bound by tax obligations. Therefore, knowledge of tax accounting is very important in planning and implementing school activities and budgets. School principals, treasurers and BOS teams must understand tax regulations related to school revenues and expenditures; such as income tax (PPh), value-added tax (VAT) and local tax. With the above premise, the author is interested in conducting research on School Financial Management in the Context of Tax Accounting: Case Study at SMP Negeri 3 Hilisalawa'ahe. The purpose of this study is to describe financial management at SMP Negeri 3 Hilisalawa'ahe, analyze the suitability of its management for tax accounting provisions, identify the obstacles faced by the financial management team of SMP Negeri 3 Hilisalawa'ahe and formulate solutions to overcome these obstacles. This research uses a qualitative approach, which is a research procedure that produces descriptive data in the form of speech or writing and observable behavior of the person (subject) itself. The data collection methods used are observation, interviews, and document review with the object of research is the financial management of SMP Negeri 3 Hilisalawa'ahe. Based on the results of the study, it was found that the Financial Management and Reporting of SMP Negeri 3 Hilisalawa'ahe is in accordance with the general provisions and procedures of taxation and there are no obstacles faced in the financial management of SMP Negeri 3 Hilisalawa'ahe because the management team is in accordance with the professional field and understands tax regulations. Translated with DeepL.com (free version).